a) x²+6x=16
x²+6x-16=0
x²+8x-2x-16=0
x(x+8)-2(x+8)=0
(x+8)(x-2)=0 x=-8 x=2
b) x²-2x=8
x²-2x=8
x²+2x-4x-8=0
x(x+2)-4(x+2)=0
(x+2)(x-4)=0 x=-2 x=4
c) 4x²-4x=8
x²-x=2
x²+x-2x-2=0
x(x+1)-2(x+1)=0
(x+1)(x-2)=0 x=-1 x=2
d) 4x²+12x=16
x²+3x=4
x²+4x-x-4=0
x(x+4)-(x+4)=0
(x+4)(x-1)=0 x=-4 x=1
e) x²-8x=-7
x²-8x+7=0
x²-x-7x+7=0
x(x-1)-7(x-1)=0
(x-1)(x-7)=0 x=1 x=7
f) x²+4x=12
x²+4x-12=0
x²+6x-2x-12=0
x(x+6)-2(x+6)=0
(x+6)(x-2)=0 x=-6 x=2
g) x²-6x=7
x²-6x-7=0
x²+x-7x-7=0
x(x+1)-7(x+1)=0
(x+1)(x-7)=0 x=-1 x=7
h) x²-4x=32
x²-4x-32=0
x²+4x-8x-32=0
x(x+4)-8(x+4)=0
(x+4)(x-8)=0 x=-4 x=8
i) x²-12x=28
x²-12x-28=0
x²+2x-14x-28=0
x(x+2)-14(x+2)=0
(x+2)(x-14)=0 x=-2 x=14